Quasi-markets, school diversity and social selection: Analysing the case of free schools in England, five years on. (17th July 2018) - Allen, Rebecca; Higham, Rob
Abstract : The opening of new state schools by non-state actors has intensified debates about social selection and inequality in quasi-markets. This article examines the case of England, where the government allows anyone to apply to open a new 'free school', arguing this will improve social equity. Using data from the National Pupil Database for all 325 free schools established between 2011/12 and 2015/16, we analyse whether the students attending free schools are representative of their local neighbourhoods. We develop the first analysis of whether the specifics of who opens and provides a free school impacts on who attends the school. We also analyse whether opening a free school has an impact on neighbouring schools. We find that free schools are located in areas with above-average deprivation but admit intakes that are more affluent than the average for the neighbourhoods from which they recruit. This is particularly the case for primary free schools, which also recruit students with above-average prior attainment. There is no evidence that free schools become more representative as they admit additional year groups. Significantly, we find that all categories of free school providers have opened schools whose populations are more affluent than their neighbourhoods, with the exception of academy chains. We also find that the opening of a free school leads to a concentrated loss of pupils at the closest school, except in cities, but we do not identify an impact on the student composition of neighbouring schools. Discussing the reasons for this, we conclude that free schools are socially selective and reproduce socio-economic inequalities.